2015
DOI: 10.1016/j.schres.2015.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging findings in treatment-resistant schizophrenia: A systematic review

Abstract: Background Recent developments in neuroimaging have advanced understanding biological mechanisms underlying schizophrenia. However, neuroimaging correlates of treatment-resistant schizophrenia (TRS) and superior effects of clozapine on TRS remain unclear. Methods Systematic search was performed to identify neuroimaging characteristics unique to TRS and ultra-resistant schizophrenia (i.e. clozapine-resistant [URS]), and clozapine's efficacy in TRS using Embase, Medline, and PsychInfo. Search terms included (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 111 publications
2
27
0
Order By: Relevance
“…These findings are consistent with the two other reviews of treatment-resistant vs treatment-responsive patients [48, 53] which identified studies demonstrating reduced grey matter; however again, the 2015 review is more cautious stating no consistent findings based on the two they discuss, while the 2016 review identifies seven studies and thus highlights reduced grey matter (particularly in frontal regions) as one of the features of treatment-resistance. The latter also suggest that these structural differences could be caused by high concentrations of glutamate, providing a plausible link between these findings within the neuroimaging literature.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are consistent with the two other reviews of treatment-resistant vs treatment-responsive patients [48, 53] which identified studies demonstrating reduced grey matter; however again, the 2015 review is more cautious stating no consistent findings based on the two they discuss, while the 2016 review identifies seven studies and thus highlights reduced grey matter (particularly in frontal regions) as one of the features of treatment-resistance. The latter also suggest that these structural differences could be caused by high concentrations of glutamate, providing a plausible link between these findings within the neuroimaging literature.…”
Section: Discussionsupporting
confidence: 85%
“…One 2015 review [53] reported the Demjaha et al findings but concluded there were no consistent findings in the field, whereas the 2016 Mouchlianitis et al review [48] reported both papers included in the present review and highlighted both elevated glutamate in the ACC and elevated Glx in the putamen of clozapine responders as features of treatment-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to better understand the potential "subtypes" of schizophrenia [103]. Such research will likely be guided by elucidating brain-specific biomarkers associated with clinical nonresponse to antipsychotics [104].…”
Section: Clarifying Our Hypothesesmentioning
confidence: 99%
“…As the quality of life in patients with TRS is remarkably disturbed through their lifespan, understanding the pathophysiology of TRS is a priority for mental health research. However, the neural basis of TRS, especially the difference from non-treatment resistant schizophrenia (nTRS), remains unclear [ 3 ].…”
Section: Introductionmentioning
confidence: 99%